BUDAYA ORGANISASI, KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN KEINGINAN BERPINDAH: INVESTIGASI EMPIRIS PADA BERBAGAI UNIT KERJA DI UNIVERSITAS BENGKULU - Nasution Nasution (Jurnal Bisnis dan Ekonomi, 2006)
The present research has two main goals, first, to re-test the dimensions of corporate culture from Hofstede et al. (1990). And second, to test the hypotheses regarding the relationship between corporate culture and employee behavior, including job saticfaction, organizational commitment, turnover intent. The sample frame is 952 respondents who serve as educative staff and administrator at the Bengkulu University. Four-hundred-and-eightyseven  respondents completed the questionnaire, resulted the 51.16% respond rate. Factor Analysis and Reliability Analysis from SPSS 12.00 were applied to test the dimensions of corporate cultureand the hypotheses were tested using SE-Path from Statistica 5.0. The 42 items questionnaire is loaded in 6 factors, as well as in Hofstede et al.’s study. Seven i tems dropped because factor loadings were less than 0.40. Another 1 item was drifted in reliability test. Therefore, the final 34 items were analyzed further with SE-Path to test the research hypotheses. Two out of 6 hypotheses are supported (hypothesis 1 and 5); 3 hypothesis are partially supported (hypothesis 2, 3, and 6); and hypothesis 4 are not supported.Keywords: corporate culture, job saticfaction, organizational commitment, turnover intent.